ASPEK TRANSENDENTAL DALAM SASTRA PROFETIK: (Novel Cinta di Ujung Sajadah Karya Asma Nadia) - Yulia Gusti, Rona; Emil Septia; Armet (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2023)
This research aims to determine the transcendental aspects of the novel by Asma Nadia entitled Cinta di Ujung Sajadah. This is very important to know because as time goes by, the achievements of Asma Nadia's learning process in understanding the facets of life, both in cultural and religious aspects, can become an inspiration for readers and this inspiration is found in every moral. message. or the message of truth in his novel to raise awareness among readers. This research uses a qualitative type with a descriptive analysis approach. The data source in this research comes from data collected in the form of words, sentences, and discourse related to the transcendental aspect studied in this novel, namely gratitude (thanks to Allah). From the results of this analysis, the researcher concluded that there were seven transcendental indicators, namely expressions of gratitude from the main character in the novel. Expressing gratitude is an important part in shaping a person's personality into a religious being who believes in the existence and power of Allah SWT. Therefore, expressing gratitude is a theme for everyone to understand their existence as God's creatures while providing a lot of goodness to others. From these conclusions, the researcher then suggests further research to dig deeper into other professional literary works, in order to understand and add new insights or references in solving problems faced in every phase of cultural and religious life